An Experiment Study to Evaluate the Effectiveness of Carom Seed Oil on reduction of Menstrual Cramps among the Adolescent girls of selected Nursing Colleges, Bangalore - Devi, Laishram Dabashini; Mary, Swapna A (Asian Journal of Nursing Education and Research, 2022)
Carom seed oil has been found to relieve the menstrual discomfort by relaxing the uterine muscles and decreasing the intra uterine pressure. Leaves and their essence are aromatic, stimulant, carminative and antispasmodic. This is also used in case of vomiting, gastric colic, diarrhea and menstrual cramps. Therefore, it was intended to do an experimental study to examine the effect of Carom seed oil on menstrual cramps with an assumption that this therapy may relieve menstrual cramps. The research design selected for the present study is experimental research design. The study was conducted in the Global College of Nursing at Bangalore. The criteria for the selection of the setting are the availability of subjects, feasibility of conducting the study. The target population in the present study was adolescent girls studying in Global College of Nursing at Bangalore. The sample of this study comprised of 60 adolescent girls. Simple random sampling (Random table number) method was used to draw the sample. A Visual Analogues Scale (VSA) to assess the pain intensity of the students. The findings revealed that in experimental group, majority of the subjects, 24 (80%) had severe pain, 6 (20%) subjects had moderate pain, none had severe pain, and in control group majority of the subjects, 22 (73.3%) had severe pain, 8 (26.6%) subjects had moderate pain, none had pain. After the intervention, in experimental group, majority of the subjects, 24 (80%) had mild pain, 6 (20%) subjects had moderate pain, none had severe and in control group majority of the subjects, 25 (83.3%) had moderate pain, 5 (16.6%) subjects had mild pain and none severe pain. The adolescent girls had reduction in the menstrual cramps as evidenced by the results shown. Hence carom seed oil is effective in the reduction of menstrual cramps and it was found to be less cost effective procedure. Therefore, carom seed oil should be used as a supportive therapy among adolescent girls to alleviate menstrual cramps.